Local Government Sustainable Development: A Theoretical Paradigm or a Plan for Action? - Phillips, Janet F.; Strickland, Pamela (Journal of Accounting, Ethics and Public Policy, 2015)
Local governments are a vital component in the national effort to promote sensible methods for community development, growth and social justice. The benefits and challenges of sustainable development have become apparent as more local governments initiate programs to address economic, environmental and social equity issues. This research investigates county and municipal government efforts toward sustainable development using survey information for local governments in the southern United States. Survey responses were analyzed to examine whether local governments “practice what they preach” in terms of actually implementing the sustainable policies proclaimed to be important to their operations. Overall, results suggest local governments do place these policies into action for environmental and social justice issues. In addition, the analysis explores the impact of population size, geographic area and form of government on sustainable development. Measuring the implementation of sustainable policies in terms of dollars, however, proves difficult because there is no consistency among municipalities with regard to reporting the amount of dollars (federal or local) spent in support of sustainability efforts.
Keywords: dept.acc; economic development; environmental protection; local government; peer-reviewed; social equity; sustainability

Accounting Majors Finish First – Results of a Five-Year Study of Performance in Introductory Accounting - Phillips, Janet F. (The Accounting Educators' Journal, 2015)
Delivery of a quality introductory accounting course is essential for schools of business. The first step in revitalization and improvement of the course is to identify factors suggested to be empirically related to succeessful completion. Accounting major status is of particular interest. While it has long been anecdotally observed and logically expected that accounting majors would earn higher grades in introductory accounting, it is rarely addressed in empirical studies. To investigate the impact of accounting major status on performance in introductory accounting, a sample of 398 students exposed to the same professor, text, teaching and examination format over five-years was gathered. Results suggest accounting major status was in fact a significant positive predictor of grades earned in the class controlling for three additional variables (i.e., grade point average, mathematics background and previous experience in the course). These results could be used to support the creation of an honors section(s) of accounting which could include a more rigorous curriculum taught with real life cases. Previous research supported the concept of an honors program from students, faculty and potential employers. In addition, the results suggest requiring a minimum grade point average and the completion of mathematics requirement before taking introductory accounting.
Keywords: dept.acc; peer-reviewed

The GAAP in Tesla’s Earnings Announcements: A Case Study on the Proliferation of Non-GAAP Financial Measures - Aselta, James; Engel, Russell Paul (The Accounting Educators' Journal, 2018)
The reporting of non-Generally Accepted Accounting Principles Measures (non-GAAP) by U.S. publically traded companies is not new but it has recently come under increased scrutiny by the United States Securities and Exchange Commission (SEC). This case presents a specific example of this scrutiny in the form of Tesla, Inc.’s quarterly earnings announcements and Tesla’s subsequent correspondence with the SEC. This case requires students to answer relevant questions about GAAP vs Non GAAP reporting, generally in the form of a research memo, with references to applicable SEC regulations and guidance on the use and reporting of non-GAAP measures.
Keywords: dept.acc; peer-reviewed

Indelible Footprints: The ICAN Story - Olutimehin, Kola; Emenyonu, Emmanuel (ICON, 2015)
Keywords: History; History; Accounting; Institute of Chartered Accountants of Nigeria; Nigeria; dept.acc; faculty_collection

Winning by His Grace: The Biography of Felix Ohiwerei - Emenyonu, Emmanuel (The Washington Nigerian Times, 2012)
Keywords: Biography; Christian biography; Biography; Nigerians; Nigeria; Ohiwerei; Felix; Businessmen; dept.acc; faculty_collection

The evolution of the relationship between the us financial accounting standards board and the international accounting standard setters: 1973-2008 - Kirsch, R.J. (Accounting Historians Journal, 2012)
Utilizing archival materials as well as personal interviews and correspondence with personnel of the Financial Accounting Standards Board (FASB) and International Accounting Standards Committee /Board (IASC/B), including former Board chairmen and staff members, this paper examines the development of the working relationships between the FASB and the IASC/B from their earliest interactions in 1973 through the transformation of the IASC into the IASB and the Convergence Program rooted in the 2002 Norwalk Agreement up to 2008. © 2012, Academy of Accounting Historians. All rights reserved.
14 citations (Crossref) [2023-10-31]
Keywords: dept.acc

Railroad audits: Some arrived ahead of schedule - Feeney, K. (Accounting Historians Journal, 2013)
Through 1975, the shareholder annual reports of publicly-owned U.S. railroads were exempt from the Securities and Exchange Commission’s accounting regulations, audit and disclosure rules because railroads were common carriers subject to the rules and regulations of the Interstate Commerce Commission (ICC). Pub-liclyowned Class railroads voluntary began to away from ICC-type towards GAAP-type accounting and disclosures in their shareholder reports just after World War II.1 This paper reviews early industry practices with respect to internal and external audits. Using a sample of major Class I railroads from 1946 to 1975, the paper shows: the extent to which certain railroads voluntarily presented audited finan-cial statements before being required, the extent to which particular CPA firms were involved with the railroad industry, and the types of audit reports that issued to these railroads during this period. © 2016, Academy of Accounting Historians. All rights reserved.
3 citations (Crossref) [2023-10-31]
Keywords: dept.acc

The role of non-governmental organizations (NGOs) as intermediaries of the European union decision to adopt international accounting standards: 1973-2002 - Kaya, D.; Kirsch, R.J.; Henselmann, K. (Accounting Historians Journal, 2016)
This paper analyzes the role of non-governmental organizations (NGOs) as intermediaries in encouraging the European Union (EU) to adopt International Accounting Standards (IAS). Our analysis begins with the 1973 founding of the International Accounting Standards Committee (IASC), and ends with 2002 when the binding EU regulation was approved. We document the many pathways of interaction between European supranational, governmental bodies and the IASC/IASB, as well as important regional NGOs, such as the Union Européenne des Experts Comptables, Économiques et Financiers (UEC), the Groupe d’Etudes des Experts Comptables de la Communauté Économique Européenne (Groupe d’Etudes), and their successor, the Fédération des Experts Comptables Européens (FEE). This study investigates, through personal interviews of key individuals involved in making the history of the organizations studied, and an extensive set of primary sources, how NGOs filled key roles in the process of harmonization of international accounting standards. © 2016, American Accounting Association. All rights reserved.
6 citations (Crossref) [2023-10-31]
Keywords: dept.acc

The GAAP in Tesla’s earnings announcements: A case study on the proliferation of Non-GAAP financial measures - Aselta, James; Engel, Russell Paul (The Accounting Educators' Journal, 2019)
The reporting of non-Generally Accepted Accounting Principles Measures (non-GAAP) by U.S. publically traded companies is not new but it has recently come under increased scrutiny by the United States Securities and Exchange Commission (SEC). This case presents a specific example of this scrutiny in the form of Tesla, Inc.’s quarterly earnings announcements and Tesla’s subsequent correspondence with the SEC. This case requires students to answer relevant questions about GAAP vs Non GAAP reporting, generally in the form of a research memo, with references to applicable SEC regulations and guidance on the use and reporting of non-GAAP measures.
Citation Key Alias: lens.org/107-162-194-311-028, pop00324 tex.type: [object Object]
Keywords: dept.acc; peer-reviewed; ⛔ No DOI found